2002
DOI: 10.1523/jneurosci.22-17-07737.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Extracellular Signal-Regulated Kinase in Primary Afferent Neurons by Noxious Stimuli and Its Involvement in Peripheral Sensitization

Abstract: Alteration in the intracellular signal transduction pathway in primary afferent neurons may contribute to pain hypersensitivity. We demonstrated that very rapid phosphorylation of extracellular signal-regulated protein kinases (pERK) occurred in DRG neurons that were taking part in the transmission of various noxious signals. The electrical stimulation of Adelta fibers induced pERK primarily in neurons with myelinated fibers. c-Fiber activation by capsaicin injection induced pERK in small neurons with unmyelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
278
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(300 citation statements)
references
References 47 publications
17
278
0
3
Order By: Relevance
“…Previous reports have suggested that inflammatory and neuropathic pain increases pERK in DRG neurons and that activation of the ERK pathway is involved in peripheral sensitization following noxious stimulation [58][59][60]. In our experiment, α, β-MeATP applied to the axon terminal for 30 min was able to increase the level of pERK as well as the depolarization-induced Ca 2+ influx in the cell bodies.…”
Section: Function Of the P2x 3 Receptor Retrograde Signalssupporting
confidence: 59%
“…Previous reports have suggested that inflammatory and neuropathic pain increases pERK in DRG neurons and that activation of the ERK pathway is involved in peripheral sensitization following noxious stimulation [58][59][60]. In our experiment, α, β-MeATP applied to the axon terminal for 30 min was able to increase the level of pERK as well as the depolarization-induced Ca 2+ influx in the cell bodies.…”
Section: Function Of the P2x 3 Receptor Retrograde Signalssupporting
confidence: 59%
“…Intradermal capsaicin also induced pERK in epidermal nerve fibers (Fig. 2h,i) and induces pERK in small-sized neurons in the DRG (Dai et al, 2002).…”
Section: Activation Of Pi3k By Capsaicin In the Drg And Skin In Vivomentioning
confidence: 80%
“…PKA and PKC appear to regulate hyperalgesia through phosphorylation and activation of TRPV1 (Premkumar and Ahern, 2000;Bhave et al, 2002) and Na V 1.8/1.9 (Gold et al, 1998;McCleskey and Gold, 1999;Julius and Basbaum, 2001;Bhave and Gereau, 2003). ERK (extracellular signal-regulated protein kinase), a member of the MAPK (mitogen-activated protein kinase) family, is activated in primary sensory neurons and epidermal nerve fibers after peripheral inflammation and contributes to inflammatory pain (Aley et al, 2001;Dai et al, 2002;Dina et al, 2003;Ji, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, propentofylline, a glial modulating agent, attenuates nerve-injury-induced mechanical allodynia at doses that inhibit both spinal microglial and astrocytic activation (28). Very little information is available regarding the intracellular signal transduction mechanisms occurring in glial cells activated during chronic pain, but recent papers provide evidence that MAP kinases play a critical role (29)(30)(31). Activation of the p38 pathway plays an essential role in production of proinflammatory cytokines such as IL-1␤, TNF-␣, and IL-6, and induction of enzymes (cyclooxygenase-2, iNOS) (32).…”
Section: Discussionmentioning
confidence: 99%